UNITY IN ACCOUNTING THEORY. - Scott, D. R. (The Accounting Review, 1931)
The accountant who looks upon accounting as a relatively finished system of technique and a relatively complete body of theory has his face turned to the past rather than to the future. He is as far out of touch with the actual situation in which we live as the economic theorist who makes the economic man the cornerstone of a supposedly universal system. As business administration becomes more professional and scientific, the relationship which has in the past prevailed between management and accounts places a two-fold burden upon accounting. It is expected to continue its function as a tool of control and at the same time it is called upon to furnish management both the facts and the principles upon which scientific administration must rest. In meeting the latter requirement it becomes essentially a scientific methodology. As such its rôle is to afford a basis for the coördination of business administration with the current scheme of economic and social organization. This discussion has dealt with potentialities of accounting development rather than with so-called actualities. It has been argued that accounts must be readjusted to a new viewpoint of management and that in order to effect such a readjustment fundamental changes of technique and rules of procedure are necessary. It has been suggested that the result desired may be obtained by a decentralization of accounting problems and a thorough functionalization of the accounting system. With our present knowledge of social phenomena, one would be rash indeed to insist that particular developments like those here suggested, must take place. There are some things, however, upon which we can depend with definite assurance. Accounting, like all other institutionalized practices, must adjust itself to a changing environment if it is to survive.